Abnormal frequency dependent polarization fatigue behavior in aged Pb(Mn1/3Sb2/3)O3-Pb(Zr, Ti)O3 ferroelectric ceramics. Issue 8 (1st June 2017) - Chen, Caiyun; Zhou, Zhiyong; Liang, Ruihong; Zhao, Xiaobo; Zhang, Wenbin; Dong, Xianlin
Abstract: The fatigue behavior of 0.05Pb(Mn1/3 Sb2/3 )O3 –0.50PbZrO3 –0.45PbTiO3 ceramics (abbreviated as PMS-PZT) is investigated. Special attention is paid to the effect of applied electric frequency on the evolution of polarization-electric field, strain-electric field hysteresis loops as well as the parameters of remnant polarization, internal bias field and coercive field extracted directly from the former hysteresis loops or calculated according to these loops. It is found that the fatigue behavior is different from that of donor doped Pb(Zr, Ti)O3 (PZT) ceramics demonstrated by the tendency of increasing remnant polarization, the decreased internal bias field, decreased asymmetry of polarization-electric and strain-electric loops with increasing fatigue duration when PMS-PZT ceramics fatigued at lower frequency (i.e. 5 Hz or 500 Hz). The dynamic of oxygen vacancies under the application of bipolar electric field is supposed to be associated with the abnormal fatigue behavior. In addition, no matter at which cyclic frequency samples fatigued, coercive field shows the tendency of decrease with increasing fatigue duration except for sample fatigued at 5 kHz in which coercive field first decreases and then increases. According to phase structure and the empirical Rayleigh analysis, phase transition during fatigue treatment is supposed to be account for the decrease of coercive field.